Microsoft Project 2016 Training (Basic & Intermediate) - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
This three-day training (6th Apr - 8th Apr 2016) was conducted by experienced instructors for lecturers who were interested in expanding their knowledge base and technical skills about Microsoft Project.